PENERAPAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Rosyda, Elya Kholilatul; Astriani, Dyah (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This research aims to compare the critical thinking skills of students on the application of guided inquiry learning model. The type of research used is quantitative research with a One Group Pretest-Posttest design. The research subjects were 31 students of class VIII-C SMPN 16 Surabaya in the academic year 2022/2023. Data collection techniques using critical thinking skills tests were analyzed by paired t test and effect size. The results showed that there was an effect of applying the guided inquiry model on critical thinking skills as evidenced by the paired t test, namely t-count > t-table or 11.61 > 2.04, then H0 was rejected and Ha was accepted and the results of the calculation of the effect size of 0.81 which is categorized as large. Based on the research results obtained, it can be concluded that the application of the guided inquiry learning model can improve students' critical thinking skills on the material of the respiratory system.